2017
DOI: 10.4049/jimmunol.1601514
|View full text |Cite
|
Sign up to set email alerts
|

Semaphorin 3E Deficiency Exacerbates Airway Inflammation, Hyperresponsiveness, and Remodeling in a Mouse Model of Allergic Asthma

Abstract: Semaphorin 3E (Sema3E) plays a crucial role in axon guidance, vascular patterning, and immune regulation. Nevertheless, the role of Sema3E in asthma is still elusive. In this study, we show that genetic ablation of Sema3E in mice results in increased lung granulocytosis, airway hyperresponsiveness, mucus overproduction, collagen deposition, and Th2/Th17 inflammation. Transfer of bone marrow progenitor cells to irradiated wild-type (WT) recipients exacerbates airway hyperresponsiveness and inflammation, whereas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
50
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 35 publications
(55 citation statements)
references
References 52 publications
5
50
0
Order By: Relevance
“…In the brain, SEMA3E is mainly produced by specific neurons (Gu & Giraudo, ; Schmidt & Moore, ; Zhou, Gunput, & Pasterkamp, ), therefore, it is possible that the destruction of enteric neurons during the colonic inflammation (Lakhan & Kirchgessner, ; Lomax et al, ; Zhou et al, ) can result in the reduction of colonic levels of SEMA3E. Furthermore, reduced levels of SEMA3E are associated with various inflammatory conditions (Movassagh, Saati, et al, ; Movassagh, Shan, Mohammed, et al, ), and genetic ablation of Sema3e in a mouse model of allergic asthma results in an aggravated inflammation associated with a massive recruitment of immune cells into the inflamed tissue (Movassagh, Shan, Mohammed, et al, ). Furthermore, we reported that colonic Sema3E level is not higher in colitic Sema3e +/+ mice compared to Sema3e −/− mice in the same condition; this could be explained by the possibility that the recombinant protein reached a maximum level in the colon and passed into the blood stream.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In the brain, SEMA3E is mainly produced by specific neurons (Gu & Giraudo, ; Schmidt & Moore, ; Zhou, Gunput, & Pasterkamp, ), therefore, it is possible that the destruction of enteric neurons during the colonic inflammation (Lakhan & Kirchgessner, ; Lomax et al, ; Zhou et al, ) can result in the reduction of colonic levels of SEMA3E. Furthermore, reduced levels of SEMA3E are associated with various inflammatory conditions (Movassagh, Saati, et al, ; Movassagh, Shan, Mohammed, et al, ), and genetic ablation of Sema3e in a mouse model of allergic asthma results in an aggravated inflammation associated with a massive recruitment of immune cells into the inflamed tissue (Movassagh, Shan, Mohammed, et al, ). Furthermore, we reported that colonic Sema3E level is not higher in colitic Sema3e +/+ mice compared to Sema3e −/− mice in the same condition; this could be explained by the possibility that the recombinant protein reached a maximum level in the colon and passed into the blood stream.…”
Section: Discussionmentioning
confidence: 99%
“…Mice heterozygous for SEMA3E expression ( Sema3e +/− ) on a mixed C57BL/6 background were used to generate Sema3e +/+ and Sema3e −/− , and Sema3e −/− was used to generate littermates. The immunophenotypic proprieties of Sema3e −/− have been described previously (Movassagh, Shan, Mohammed, et al, ). Male Sema3e −/− (20–25 g, 6–8 weeks old; IMSR Cat# KOMP:VG14098‐1‐Vlcg, RRID:IMSR_KOMP:VG14098‐1‐Vlcg) were obtained from the animal facility at the University of Manitoba and used according to the guidelines of the Canadian Council on Animal Care in science.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…It will be more appreciated if this model could clearly display a mucus hyperproduction as in the allergen-induced asthma model. If this could be realized, then a long-time self-antigen challenge should lead to the airway remodeling and emphysema-like airspace enlargement and eventually result in declined lung function, as does by allergens in the models of asthmatic airway remodeling [98, 99]. …”
Section: Conclusion and A Perspectivementioning
confidence: 99%